Enabling success at university: the impact of an Australian programme to provide access to university. Issue 1 (2nd January 2020) - Taylor, Janet A.; van Eyk, Tina; Syme, Suzi
ABSTRACT: In Australia access to university studies is supported through students' participation in government funded, pre-award programmes called 'enabling' programmes. These programmes allow students to meet university entry requirements and are designed to prepare students for the rigours of study. This article explores the performance and experience of students studying a range of undergraduate degrees after completing an enabling programme in a regional Australian university. Institutional data confirmed that post-enabling students in this study performed better in undergraduate programmes than traditionally enrolled students when grade point average (GPA), success and retention rates were compared. Students' beliefs about the reason for this success were clustered within the six themes of confidence, ways of studying, managing lifeload, skills obtained, their attitudes to study, and the enabling programme staff and teaching. Students openly discussed their challenges and skills gained, and demonstrated confidence and resilience in undergraduate study. Staff reflections highlighted similar themes to those of the students, although in a different sequence of importance. Taken together, these three sets of results confirm that students who completed the enabling programme in this study were likely to succeed both personally and in their programmes of future study.